PARIWISATA BERBASIS MASYARAKAT: LANGKAH TEPAT KEBERLANJUTAN? - Putra, Septian Asriadi; Fatmasari, Baiq Rizky; Annisa, Lintang; Furqan, Alhilal (Jurnal Master Pariwisata (JUMPA); Volume 10, Nomor 01, Juli 2023, 2023)
Tourism is considered one of the great opportunities in development. However, it needs to be remembered that tourism will invite large capital to enter, which can produce other consequences. Community-based tourism is one model that is expected to accommodate local interests and involvement. Indonesia is promoting this activity in the form of Desa Wisata and several other forms. Based on this debate, a study was conducted that identified community-based tourism activities in Pasir Angling Village, West Java. It was found that tourism activities carried out by the community are a form of community-based tourism. In this study, it was concluded that the fulfillment of most of the indicators indicated that there were community-based tourism activities. This research implies that the activities carried out are indeed potentially very good with a note that this activity is a development activity, not the main one. In addition, the distribution of resources owned by the community can be used as new potential as a form of income diversification. Another important thing is that capital and financial results are not very important with the togetherness built by the whole community. This research was taken from the perspective of the researcher as a tourist. Thus, it has not measured the actual impact of the implementation of community-based tourism activities in Pasir Angling Village. Future research is very open to be carried out. Keywords: community based tourism; sustainability; Indonesia.